2022
DOI: 10.1177/13623613221140749
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and commitment therapy for autistic adults: A randomized controlled pilot study in a psychiatric outpatient setting

Abstract: Autistic adults are at risk of stress-related psychiatric disorders and reduced life quality due to social, cognitive, and perceptual challenges. Mental health interventions adapted to autistic adults are scarce. Acceptance and commitment therapy has preliminarily indicated health benefits in autistic adults, although it has not been robustly evaluated. Overall, 39 adults (21 males; 21–72 years) with autism spectrum disorder and normal intellectual ability ( IQ M = 108.5; SD = 13.5) were randomized to 14 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…Results showed that omega fatty acids reduced anxious and depressive behaviors and improved social interactions, but did not have any effect on sleep (the effect size was small and statistically non-significant). Similarly, a meta-analysis of randomized controlled trials conducted to test the effects of polyunsaturated fatty acids (PUFAs) on several outcomes in children and adolescents with autism found uncertain evidence of PUFAs worsening the quality of sleep [49] . However, the authors recommended that more studies shall be conducted, considering the very low quality of the studies included.…”
Section: Children and Adolescentsmentioning
confidence: 99%
“…Results showed that omega fatty acids reduced anxious and depressive behaviors and improved social interactions, but did not have any effect on sleep (the effect size was small and statistically non-significant). Similarly, a meta-analysis of randomized controlled trials conducted to test the effects of polyunsaturated fatty acids (PUFAs) on several outcomes in children and adolescents with autism found uncertain evidence of PUFAs worsening the quality of sleep [49] . However, the authors recommended that more studies shall be conducted, considering the very low quality of the studies included.…”
Section: Children and Adolescentsmentioning
confidence: 99%